2016
DOI: 10.1248/bpb.b16-00266
|View full text |Cite
|
Sign up to set email alerts
|

Nano-biomechanical Validation of Epithelial–Mesenchymal Transition in Oral Squamous Cell Carcinomas

Abstract: The effective cure for oral squamous cell carcinoma (OSCC) patients is challenging due late diagnosis and fatal metastasis. The standard diagnosis for OSCC often depends on the subjective interpretation of conventional histopathology. Additionally, there is no standard way for OSCC prognosis. Over the past decade, nano-mechanical stiffness has been considered as a quantitative measure for cancer diagnosis. Nevertheless, its application to OSCC diagnosis and prognosis is still in a primitive stage. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…ZEB1 is abnormally expressed in various human cancers and is best known for activating EMT in cancer cells to facilitate tumor development [ 28 ]. In recent years, a growing body of evidence has shown that EMT is involved in the pathogenesis of OSCC [ 29 , 30 ]. As a crucial transcription factor of EMT regulation, we speculated that ZEB1 might play a critical role in the pathogenesis of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 is abnormally expressed in various human cancers and is best known for activating EMT in cancer cells to facilitate tumor development [ 28 ]. In recent years, a growing body of evidence has shown that EMT is involved in the pathogenesis of OSCC [ 29 , 30 ]. As a crucial transcription factor of EMT regulation, we speculated that ZEB1 might play a critical role in the pathogenesis of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is the seventh most common cancer in the world, with ~600,000 cases each year. The 5-year survival rate is generally <50% (1,2). HNSCC is divided into two types, human papilloma virus (HPV)-positive and HPV-negative, which is dependent on whether HNSCC is caused by HPV (3).…”
Section: Introductionmentioning
confidence: 99%
“…Confined environment can modulate the behavior of mesenchymal or EMT cells by inducing a mesenchymal to amoeboid transition in low adhesion conditions, allowing cancer cells to adapt their migration mode to their environment. Interestingly, studies aiming at measuring the mechanical properties of oral squamous cell carcinoma as they undergo EMT have demonstrated a general softening of cells as the EMT progresses (Park et al 2016). This, along with other similarly reported data, suggests that in environments with high mechanical constraints (like the stiff ECM of confined space), cells modulate their inner mechanical properties to become softer by undergoing an EMT process.…”
Section: Biomechanical Considerations Of Emt In Cancermentioning
confidence: 66%